Characteristic of activity of enterprises of the fuel and energy complex of Russia on introduction of innovation technologies and equipment Характеристика деятельности предприятий топливно-энергетического комплекса России по внедрению инновационных технологий и оборудования - Katysheva Yelena G. (Problemi Ekonomiki, 2013)
Competitiveness of enterprises of the fuel and energy complex of Russia is determined now by efficiency of innovation activity. Technological innovations that are capable of increasing efficiency of development of hydrocarbons are developed and offered for introduction at all stages: from survey and exploration to processing of petroleum and natural gas. Конкурентоспособность предприятий топливно-энергетического комплекса (ТЭК) России в настоящее время определяется эффективностью инновационной деятельности. Технологические инновации, способные повысить эффективность освоения углеводородов, сегодня разработаны и предложены для внедрения на всех стадиях: от поиска и разведки до переработки нефти и газа.